Social inequality, city shrinkage and city growth in Khuzestan Province, Iran. Issue 2 (3rd August 2016) - Pourahmad, Ahmad; Khavarian-Garmsir, Amir Reza; Hataminejad, Hossein
ABSTRACT: The phenomenon of urban shrinkage is found in developing as well as in developed countries but the patterns differ. In developing countries, socio-economic inequality can explain population mobility between cities. A comparative study of shrinking and growing cities in Khuzestan Province in Iran showed that social conditions in the former were significantly worse than in the latter and that these conditions played an important role in the decisions of residents to leave. The impacts of the Iran-Iraq war, post-war reconstruction and the attractiveness of some cities such as Ahvaz (the provincial capital), Tehran, Esfahan, and Shiraz played a part.